OP0121 The Frequency of Bone Erosion and Oedema in Inflammatory and Degenerative Arthropathies Proximal to the Peri-Entheseal Cruciate Ligament Vascular Channels. (23rd January 2014) - Binks, D.; Matzelle, M.; Bergin, D.; Hodgson, R.; Gravallese, E.; McGonagle, D.; Radjenovic, A.
Abstract : Background: We noted in mouse models of inflammatory arthritis (IA) that an early point of entry of inflammation into the marrow space occurs at sites where penetrating vessels entered the bone. The role of penetrating vessels in erosion formation in man has not been explored in IA, nor has the role of vascular channels in bone oedema in osteoarthritis (OA) been explored. Objectives: The purpose of this work was to investigate the frequency of bone erosion and oedema in inflammatory and degenerative arthropathies in close proximity to the peri-entheseal ACL and PCL vascular channels. Methods: Normal microanatomy was defined in 21 cadaveric knees using 3T MRI and histology. MRI of 89 patients from the Osteoarthritis Initiative study and 27 patients with inflammatory arthritis were evaluated for erosion and bone oedema at the same locations. Two animal models of inflammatory arthritis were evaluated to ascertain whether the putative peri-entheseal vascular regions influenced the propensity of osteitis and bone erosion. Results: Data from the two animal models of IA showed inflammation entering the marrow space along the adventitia of blood vessels that penetrate the cortical bone in close proximity to the cruciate ligament insertions. On 3T MRI, a vascular channel adjacent to the ACL tibial insertion was observed in 64% of cadaveric specimens examined. Similarly, a vascular channel adjacent to the PCL was seen in 71% of cases. Bone marrow oedema was observed in the regions corresponding to the location of the vascular channel in 51% of knees for both the anterior and posterior channel. Histological evaluation of 10 cadaveric specimens confirmed the location of the vascular channels along with the presence of associated subclinical microdamage including subchondral bone erosion (80% of cases) and micro-cyst formation (50%). Evaluation of patient MRIs showed the prevalence of oedematous features in the same topographic locations in patients with early OA (41% ACL, 59% PCL) and inflammatory arthritis (44% ACL, 33% PCL), (figure 1 ). Image/graph: Conclusions: Our findings show that the vascular channels adjacent to the anterior and posterior cruciate ligament entheses are common locations for erosion formation and damage in both inflammatory and degenerative arthritis. Furthermore, we have found a significant clustering of subclinical microdamage in these regions in normal cadaveric samples. Therefore, we conclude that peri-entheseal vascular channels are likely to present a common pathogenesis focus for both OA and IA. Disclosure of Interest: None Declared